A glucose electrode using high-stability glucose-oxidase collagen membranes - Thevenot, D.R.; Sternberg, R.; Coulet, P. (Diabetes Care, 1982)
A very sensitive glucose electrode was developed using a glucose-oxidase membrane and an anodically polarized platinum disk. Calibration curves were linear over 4,5 concentration decades. It was adapted for human blood samples. The lifetime of glucose-oxidase collagen membranes was greater than 3 yr at 4°C and was \textasciitilde6 mo at 20-30°C.